Characterising a biologically relevant protein-G4 interaction : HP1α and TERRA : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University, Palmerston North, New Zealand - Roach, Ruby (Massey University, 2019)
Our genetic material is intricately folded and protected through the formation of a compact nucleoprotein complex, termed heterochromatin. In addition to controlling the expression of genes, heterochromatin formation is important for the structural integrity of our genome, speciﬁcally for the centromeres, the central attachment point of our chromosomes, and also the telomeres, the ends of our chromosomes. The way in which the heterochromatin in these areas is formed and maintained is though the recruitment and binding of the pivotal chromatin regulator, Heterochromatin Protein 1α (HP1α). The current model that explains how and why HP1α is recruited to, and maintained at, regions of constitutive heterochromatin is simple: HP1α binds post-translational modiﬁcations on histones (eg. H3K9me3). However, this binding is not high aﬃnity, therefore may not be the sole determinant in HP1α localisation. At the centromeres, it has been shown that a long non-coding RNA transcribed from the peri-centromeres is responsible for recruiting HP1α to this crucial region. At the telomeres, it is proposed that the long non-coding RNA transcribed from the telomeric DNA is responsible for this same purpose. Because of its guanine-rich sequence, it is able to form a non-canonical nucleic acid structure, the G-quadruplex, which may provide the speciﬁcity for heterochromatin formation at telomeres. This TElomeric Repeat-containing RNA (TERRA) has been implicated in telomeric elongation pathways, relating it to the immortalisation of cancer cells. It was found that HP1α can speciﬁcally recognise the parallel topology of TERRA, binding with high aﬃnity through HP1α’s unstructured hinge. HP1α was also shown to bind other G-quadruplexes of parallel topology, speciﬁcally DNA present in promoter and regulatory regions of many proto-oncogenes, implicating HP1α in potential G-quadruplex-dependent gene expression regulatory mechanisms. The interaction shown here between HP1α and TERRA shows a novel mechanism of telomeric heterochromatin formation, providing crucial insights into telomere maintenance and health in human cells, and furthering our understanding of the role of G-quadruplexes in the epigenome.
Keywords: Heterochromatin; Chromosomal proteins; Non-coding RNA; Telomere; Quadruplex nucleic acids; 310508 Genome structure and regulation